Legal Analysis of the Ammar Zoni Case: A Restorative and Collaborative Justice Perspective - Steven Abednego Panggabean; Mompang L Panggabean; Rospita Adelina Siregar (Bacarita Law Journal, 2026)
This article examines the legal controversy surrounding the Ammar Zoni narcotics case through the perspectives of Restorative Justice and Collaborative Justice. As a public figure, his case generated extensive debate regarding the appropriateness of alternative justice mechanisms, particularly in relation to recidivism, systemic integrity, and the role of offenders in exposing broader institutional misconduct. The purpose of this study is to analyze the legal feasibility of applying Restorative Justice and Justice Collaborator mechanisms in the Ammar Zoni case. Specifically, it aims to assess whether these approaches can be legitimately employed in cases involving repeated offenses, public figures, and allegations of systemic corruption within law enforcement institutions. This research adopts a normative juridical method using a doctrinal legal approach. It relies on statutory analysis, case-based reasoning, and conceptual interpretation of restorative and collaborative justice principles. Primary legal materials, judicial practices, and scholarly literature are examined to evaluate the legal standards governing the application of Justice Collaborator status and restorative mechanisms in Indonesia. The findings demonstrate that the application of Restorative Justice in this case is legally untenable due to recidivism and the gravity of the offense. Conversely, Justice Collaborator status remains conditionally viable, depending on verifiable contributions. This study introduces a novel perspective by framing collaborative justice as a potential instrument for exposing systemic wrongdoing within law enforcement institutions.